Subclinical Inflammation of the Ocular Surface in Soft Contact Lens Wear. Issue 2 (February 2020) - Saliman, Noor Haziq; Morgan, Philip B.; MacDonald, Andrew S.; Maldonado-Codina, Carole
Abstract : Purpose: To investigate the inflammatory response of the ocular surface with different soft contact lens (CL) replacement frequencies and materials. Methods: Twenty soft CL wearers were required to wear 3 lens types: reusable Acuvue 2 (A2), reusable Acuvue Oasys (AO), and daily disposable Acuvue Oasys (AODD), for 1 week in random sequence in 1 eye with the nonlens-wearing eye acting as a control. Three methods were used to assess the subclinical response: tear cytokine evaluation, in vivo confocal microscopy (IVCM), and impression cytology. Results: Of 13 cytokines investigated, differences were observed only for IL-12p70, which was present in greater concentrations for A2 (interocular difference 8.8 pg/mL, 95% confidence interval 5.5–12.1) and AO (8.9 [5.7–12.1]) compared with AODD (3.7 [0.6–6.8]). For IVCM, corneal presumed dendritic cell density was lower for AODD (interocular difference 1.9 [−0.1 to 3.9] cells/mm 2 ) than for both A2 (9.3 [7.2–11.4]) and AO (10.6 [8.6–12.6]). This trend was the same for the other 5 IVCM measures evaluated. The proportion of CD45 + cells in the bulbar conjunctiva was lower for AODD (0.6 [−0.3 to 1.5]%) compared with A2 (4.6 [3.7–5.6]) and AO (4.8 [3.9–5.8]). Similar findings were observed for cells in the upper lid margin. Conclusions: This work has demonstrated for the first time that daily disposable CL wear produces a minimal subclinical inflammatory response compared with no lens wear over 1 week. By contrast, this inflammatory response is upregulated with reusable lenses but appears to be similar between hydrogel and silicone hydrogel materials over this short time frame.